The effect of slip condition on heat transfer of MHD oscillatory third orderfluid flow in a channel filled with porous medium - Hamdi, Hala; Abdulhadi, Ahmed (Iraqi Journal of Science, 2024)
The combined effect of a transverse magnetic field and radiative heat transfer tounsteady flow of a conducting optically third order fluid through a channel filled withsaturated porous medium and non-uniform walls temperature is investigated.It isassumed that the no-slip condition between the wall and the fluid remains no longervalid. The third order fluid equations of continuity momentum and energy are obtained.Analytical solutions for problem are established.The effect of wall slip on velocity fieldis presented by figures. The basic properties of the flow are studied.